2022
DOI: 10.1186/s12967-022-03502-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle miR-32 derived from macrophage promotes arterial calcification in mice with type 2 diabetes via inhibiting VSMC autophagy

Abstract: Background The development of diabetes vascular calcification (VC) is tightly associated with the inhibition of vascular smooth muscle cell (VSMC) autophagy. Previously, our team found that miR-32-5p (miR-32) promotes macrophage activation, and miR-32 is expressed at higher level in the plasma of patients with coronary calcification. However, whether miR-32 mediates the function of macrophages in type 2 diabetes (T2D) VC is still unclear. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(48 reference statements)
0
12
0
1
Order By: Relevance
“…T2D mice were generated as previously reported. 19 , 20 Mice were group housed (2–5 mice per cage) at a controlled temperature (22 ± 2°C) under a 12‐h light/dark cycle with free access to food and water. The mice adapted to their new environment for 7 days before the behavioral tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T2D mice were generated as previously reported. 19 , 20 Mice were group housed (2–5 mice per cage) at a controlled temperature (22 ± 2°C) under a 12‐h light/dark cycle with free access to food and water. The mice adapted to their new environment for 7 days before the behavioral tests.…”
Section: Methodsmentioning
confidence: 99%
“… 17 We previously confirmed that peripheral macrophages in T2D patients are prone to polarize into the M1 phenotype and secrete inflammatory factors and extracellular vesicles to promote VC. 18 , 19 , 20 Are macrophages also the key target cells of BF to promote T2D VC?…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ uptake by cells via exosomes or Ca 2+ channels further contributed to an increase in Nox5 activity (90). Under hyperglycaemic conditions, EV miR-32 in macrophages was upregulated and delivered to VSMCs, promoting osteogenic differentiation and inhibiting autophagy in VSMCs via the miR-32/Mef2d/cGMP-PKG signaling pathway (91). Lipoprotein(a) stimulation led to an increase in the annexin level in the EV cargo of primary human smooth muscle cells (SMCs) and valvular interstitial cells (VICs), and these EVs readily aggregated in the collagen matrix and induced its mineralization, leading to the formation of microcalcifications that coalesced into macrocalcifications (92).…”
Section: Exosomes and Vascular Calcificationmentioning
confidence: 99%
“…Severe vascular calcification in diabetic has also been confirmed to be related to VSMCs ( 117 , 118 ). In addition, AGEs ( 119 , 120 ), apoptosis ( 121 , 122 ), oxidative stress ( 123 , 124 ) and a variety of noncoding RNAs ( 125 , 126 ) regulate AS under diabetic state. Recent studies about the effect of high glucose on VSMCs was listed in Table 3 .…”
Section: Diabetes and Vsmcsmentioning
confidence: 99%